2011
DOI: 10.1016/j.jsps.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Designing an extended release waxy matrix tablet containing nicardipine–hydroxy propyl β cyclodextrin complex

Abstract: The prepared waxy matrix tablet containing NC complexes with CD shows promising results as extended release tablets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The spectrum of PVP presented peaks at 3452.2 , 2926.5, 1663.4, 1415.7, and 1290.1 cm −1 that were attributed to N-H, CH 2 , C=O, C-N stretching vibration, and C-H bending, respectively (29). The peaks at 3423.7, 2915.4, 1167.8, and 1083.7 of the HPβCD spectrum corresponded to O-H, C-H, C-H, and C-O stretching vibrations, respectively (30). The pure PVP/HPβCD nanofiber mats exhibited absorption peaks as observed in the spectra of PVP and HPβCD.…”
Section: Ft-ir Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…The spectrum of PVP presented peaks at 3452.2 , 2926.5, 1663.4, 1415.7, and 1290.1 cm −1 that were attributed to N-H, CH 2 , C=O, C-N stretching vibration, and C-H bending, respectively (29). The peaks at 3423.7, 2915.4, 1167.8, and 1083.7 of the HPβCD spectrum corresponded to O-H, C-H, C-H, and C-O stretching vibrations, respectively (30). The pure PVP/HPβCD nanofiber mats exhibited absorption peaks as observed in the spectra of PVP and HPβCD.…”
Section: Ft-ir Analysismentioning
confidence: 96%
“…The samples of the herbal oil loaded nanofiber mats with varied oil were incubated with Candida suspensions under agitation at 37°C. After the predetermined contact times (5,15,30,60, and 120 min), small aliquots of the samples were removed, and the microorganisms were counted by spreading each sample onto an SDA agar plate. The plates were incubated for 24 h, and the viable colonies were counted.…”
Section: Time-kill Curve Studiesmentioning
confidence: 99%
“…Table 4. The mean yield pressure, P y , is inversely related to the formulations ability to deform plastically under pressure [21,22]. The P y values showed that MCC PH 101 has the lowest while APS exhibited the highest.…”
Section: Dilution Potential Propertiesmentioning
confidence: 99%
“…This indicates that there was no chemical interaction between the drug and excipients used. FTIR spectroscopy is an important tool used to assess the interaction between excipients and guest molecules in the solid state which can be revealed as shifts disappearances or changes in the absorption spectrum of the API [2,21].…”
Section: Compaction and Compressibility Characteristicsmentioning
confidence: 99%
“…Natural polymer chitosan is known for its permeability enhancement through mucosal membrane and will enhance drug absorption. This in turn will reduce the dose size and dosing frequency and subsequently will result in result in efficient drug therapy and patient compliance [13][14][15][16][17][18][19][20]…”
Section: Introductionmentioning
confidence: 99%